Trends in tobacco and alcohol brand placements in popular US movies, 1996 through 2009 - Bergamini, Elaina; Demidenko, Eugene; Sargent, James D (JAMA pediatrics, 2013)
Tobacco and alcohol use in movies could be influenced by product placement agreements. Tobacco brand placement was limited by the Master Settlement Agreement (MSA) after 1998, while alcohol is subject to self-regulation only. To examine recent trends for tobacco and alcohol use in movies. We expected that the MSA would be associated with declines in tobacco but not alcohol brand placement (hypothesis formulated after data collection). Content analysis. Top 100 box-office hits released in the United States from 1996 through 2009 (N = 1400). The MSA, an agreement signed in 1998 between the state attorneys general and tobacco companies, ended payments for tobacco brand placements in movies. Trend for tobacco and alcohol brand counts and seconds of screen time for the pre-MSA period from 1996 through 1999 compared with the post-MSA period from 2000 through 2009. Altogether, the 1400 movies contained 500 tobacco and 2433 alcohol brand appearances. After implementation of the MSA, tobacco brand appearances dropped exponentially by 7.0% (95% CI, 5.4%-8.7%) each year, then held at a level of 22 per year after 2006. The MSA also heralded a drop in tobacco screen time for youth- and adult-rated movies (42.3% [95% CI, 24.1%-60.2%] and 85.4% [56.1%-100.0%], respectively). In contrast, there was little change in alcohol brand appearances or alcohol screen time overall. In addition, alcohol brand appearances in youth-rated movies trended upward during the period from 80 to 145 per year, an increase of 5.2 (95% CI, 2.4-7.9) appearances per year. Tobacco brands in movies declined after implementation of externally enforced constraints on the practice, coinciding also with a decline in tobacco screen time and suggesting that enforced limits on tobacco brand placement also limited onscreen depictions of smoking. Alcohol brand placement, subject only to industry self-regulation, was found increasingly in movies rated for youth as young as 13 years, despite the industry's intent to avoid marketing to underage persons.